Validity and Agreement of Uveitis Experts in Interpretation of Ocular Photographs for Diagnosis of Behcet Uveitis - AKMAN, MEHMET (TAYLOR & FRANCIS INC, 2014)
Purpose: To evaluate agreement and estimate sensitivity and specificity of uveitis specialists' interpretation of ocular photographs in diagnosing Behcet uveitis. Methods: Fourteen Turkish uveitis specialists, masked to demographic and clinical features of patients, independently labeled ocular photographs (29 Behcet/30 other diagnoses) as Behcet uveitis or non-Behcet. Level of agreement was evaluated using kappa statistics. Photographs were categorized based on ocular signs captured and performance of observers. Results: Exact agreement with the correct diagnosis was 56-81%. Seven reviewers correctly labeled more than 70% of photographs. Interobserver agreement among those 7 reviewers revealed moderate (kappa = 0.41-0.60) or substantial (kappa = 0.61-0.80) agreement in 76% of pairs. Smooth layered hypopyon, superficial retinal infiltrate with retinal hemorrhages, and branch retinal vein occlusion with vitreous haze were correctly recognized as Behcet uveitis by majority of reviewers. Conclusions: There are ocular signs of Behcet disease that can be considered diagnostic even in the absence of any other clinical information.
Keywords: Behcet uveitis; diagnosis; expert agreement; ocular photographs; uveitis; SILK ROAD; DISEASE; CRITERIA; INVOLVEMENT; MANAGEMENT; RETINITIS